1997
DOI: 10.1136/jnnp.63.2.152
|View full text |Cite
|
Sign up to set email alerts
|

Constraints on the cerebral basis for semantic processing from neuroimaging studies of Alzheimer's disease

Abstract: Objective-Functional activation studies of semantic processing in healthy adults have yielded conflicting results. The purpose was to evaluate the relative role of the brain regions implicated in semantic processing with converging evidence from imaging studies of patients with impaired semantic processing. Methods-Semantic memory was assessed in patients with Alzheimer's disease using two measures, and these performance patterns were related to profiles of reduced cerebral functioning obtained with high resol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
39
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(47 citation statements)
references
References 51 publications
8
39
0
Order By: Relevance
“…Interaction analyses revealed that a network including the left temporoparietal and inferior frontal regions was significantly less recruited in AD patients than in the control group, when comparing word to WL2 nonword conditions. This result is in keeping with previous neuroimaging findings showing a correlation between semantic deficits in AD patients and impairment of left temporoparietal areas, as measured by structural MRI or resting brain metabolism [Desgranges et al, 1998;Grossman et al, 1997Grossman et al, , 1998]. As suggested by Grossmann et al [2003], impaired activity in the left temporoparietal and frontal regions in AD patients could reflect impaired integration of lexicosemantic information, regardless of the domain of knowledge or the nature of the task.…”
Section: Cortical Activation For Lexicosemantic Representations In Adsupporting
confidence: 91%
“…Interaction analyses revealed that a network including the left temporoparietal and inferior frontal regions was significantly less recruited in AD patients than in the control group, when comparing word to WL2 nonword conditions. This result is in keeping with previous neuroimaging findings showing a correlation between semantic deficits in AD patients and impairment of left temporoparietal areas, as measured by structural MRI or resting brain metabolism [Desgranges et al, 1998;Grossman et al, 1997Grossman et al, , 1998]. As suggested by Grossmann et al [2003], impaired activity in the left temporoparietal and frontal regions in AD patients could reflect impaired integration of lexicosemantic information, regardless of the domain of knowledge or the nature of the task.…”
Section: Cortical Activation For Lexicosemantic Representations In Adsupporting
confidence: 91%
“…focal lesions, semantic dementia, Coughlan and Warrington, 1978;Grossi et al, 1988;Hodges et al, 1992) and activation studies during semantic tasks (for review, see Buckner and Tulving, 1995). Our findings also agree with earlier related work in demented patients (Foster et al, 1983;McGeer et al, 1990;Perani et al, 1993;Slansky et al, 1995; see also the recent report by Grossman et al, 1997). Finally, our observations of a preferential involvement of the left temporoparietal cortex in semantic fluency and the left prefrontal cortex in formal fluency concurs with the principles of these tasks, as well as with the PET activation study of Mummery et al (1996) in healthy subjects.…”
Section: Verbal Semantic Memorysupporting
confidence: 82%
“…the tests used were not targeted in a prospective manner on particular memory systems, while the possible confounding effect of age (Duara et al, 1984;Eustache et al, 1995) was rarely considered. Recent studies (Collette et al, 1997;Grossman et al, 1997) aimed at identifying the cerebral regions underlying memory deficits, but they were each limited to one system only (short-term and semantic memory, respectively). Only Perani et al (1993) studied several memory systems with reference to an organizational model of memory (Squire and Zola-Morgan, 1991) and found significant associations between memory scores and CMRGlc values in various regions of interest by means of multivariate analysis.…”
Section: Introductionmentioning
confidence: 99%
“…This distribution of disease results in difficulty in retrieving information from familiar categories ("semantic memory") in 30% to 50% of AD patients (Grossman et al, 1996). Several imaging studies with AD patients have shown correlations between difficulty in semantic-mmory retrieval and functional cortical defects in dorsolateral prefrontal and posterolateral temporal-parietal cortices (Grossman et al, 1997;Desgranges et al, 1998). Thus there is abundant evidence that AD patients have difficulties in using familiar categories.…”
Section: Using Novel Categories: Patient Studiesmentioning
confidence: 99%